Variations in flowering phenology and reproductive success in Setaria lachnea - Exner, Eliana de Luján (2010)
Setaria lachnea, moha perenne, is a native grass with excellent forage quality; thus, its introduction to cultivation has been recommended. Therefore, in the present study, the variability in flowering phenology and reproductive success of three Argentine populations from different places by altitudinal gradient have been analyzed, with respect to points of interest for selecting materials. A completely randomized experimental design was used, with 10 genotypes per population and 3 replications per genotype. Flowering phenology was analyzed through variables of flowering start and mid-flowering; the number of panicles was quantified by observation, the number of the total of panicles and reproductive success by fruiting percentage. For flowering start only significant (p£0.05) intrapopulation variations were found. Seventy-five percent of the genotypes started flowering in November 2005. For mid-flowering, there were significant inter- and intra-population differences (p£0.05). The intrapopulation variability observed will allow selecting genotypes with prolonged vegetative period. Reproduction success, measured as mean fruiting percentage, was 41 (high for a nondomesticated species), with variation from 3 % to 80 %. In the two analyzed years (2005-2006), significant inter- and intra-population differences (p£0.05) were found. Genotypes of the population of less height stood out by their high fruiting percentage, always above 40 %; however, there was no variation pattern associated to altitude. Beginning of flowering was not correlated with fruiting percentage; therefore, it will be possible to select late-ripening materials, without altering fruiting percentage. , moha perenne, is a native grass with excellent forage quality; thus, its introduction to cultivation has been recommended. Therefore, in the present study, the variability in flowering phenology and reproductive success of three Argentine populations from different places by altitudinal gradient have been analyzed, with respect to points of interest for selecting materials. A completely randomized experimental design was used, with 10 genotypes per population and 3 replications per genotype. Flowering phenology was analyzed through variables of flowering start and mid-flowering; the number of panicles was quantified by observation, the number of the total of panicles and reproductive success by fruiting percentage. For flowering start only significant (p£0.05) intrapopulation variations were found. Seventy-five percent of the genotypes started flowering in November 2005. For mid-flowering, there were significant inter- and intra-population differences (p£0.05). The intrapopulation variability observed will allow selecting genotypes with prolonged vegetative period. Reproduction success, measured as mean fruiting percentage, was 41 (high for a nondomesticated species), with variation from 3 % to 80 %. In the two analyzed years (2005-2006), significant inter- and intra-population differences (p£0.05) were found. Genotypes of the population of less height stood out by their high fruiting percentage, always above 40 %; however, there was no variation pattern associated to altitude. Beginning of flowering was not correlated with fruiting percentage; therefore, it will be possible to select late-ripening materials, without altering fruiting percentage.